2013
DOI: 10.1093/gbe/evt176
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Organization and Differential Signature of Positive Selection in the Alpha and Beta Globin Gene Clusters in Two Cetacean Species

Abstract: The hemoglobin of jawed vertebrates is a heterotetramer protein that contains two α- and two β-chains, which are encoded by members of α- and β-globin gene families. Given the hemoglobin role in mediating an adaptive response to chronic hypoxia, it is likely that this molecule may have experienced a selective pressure during the evolution of cetaceans, which have to deal with hypoxia tolerance during prolonged diving. This selective pressure could have generated a complex history of gene turnover in these clus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 57 publications
(68 reference statements)
1
12
0
Order By: Relevance
“…Elevated concentrations of respiratory pigments have obvious adaptive advantages for maintaining aerobic metabolism in diving birds and mammals, and recent studies have examined the potential adaptive molecular evolution of the functional properties of these pigments Soegaard et al, 2012;Helbo and Fago, 2012;Schneuer et al, 2012;Mirceta et al, 2013). Oxygen binding globin proteins are obvious candidates for molecular adaptation in diving animals that experience regular hypoxia (Nery et al, 2013a) and Mb has experienced an increased rate of evolution in cetaceans (Nery et al, 2013b). Dasmeh et al (2013) found that mutations that increase Mb protein-fold stability are positively selected for in cetaceans, and this increase in protein stability is positively correlated with Mb concentration.…”
Section: Mb Structural Variants and Oxygen Affinitymentioning
confidence: 99%
“…Elevated concentrations of respiratory pigments have obvious adaptive advantages for maintaining aerobic metabolism in diving birds and mammals, and recent studies have examined the potential adaptive molecular evolution of the functional properties of these pigments Soegaard et al, 2012;Helbo and Fago, 2012;Schneuer et al, 2012;Mirceta et al, 2013). Oxygen binding globin proteins are obvious candidates for molecular adaptation in diving animals that experience regular hypoxia (Nery et al, 2013a) and Mb has experienced an increased rate of evolution in cetaceans (Nery et al, 2013b). Dasmeh et al (2013) found that mutations that increase Mb protein-fold stability are positively selected for in cetaceans, and this increase in protein stability is positively correlated with Mb concentration.…”
Section: Mb Structural Variants and Oxygen Affinitymentioning
confidence: 99%
“…Compared to hypoxic tolerance in terrestrial mammals, such as plateau and cave mammals which adapt to chronic hypoxia, cetaceans have adapted to fluctuating oxygen [22, 23], but how this occurs is unclear [24, 25]. …”
Section: Introductionmentioning
confidence: 99%
“…To more precisely identify the possible origin of haplotype B , we collected the sequences of the beta‐globin loci from all of the available ruminant genomes as well as from the killer whale and bottlenosed dolphin, which like the ruminants also belong to the cetartiodactyls (Nery et al . ). The pig and wild Bactrian camel were also used as outgroups.…”
Section: Resultsmentioning
confidence: 97%